Detection of Spontaneous FeOOH Formation at the Hematite/Ni(Fe)OOH Interface During Photoelectrochemical Water Splitting by Operando X‑ray Absorption Spectroscopy - Ismail, Ahmed S. M; Garcia-Torregrosa, Ivan; Vollenbroek, Jeroen C; Folkertsma, Laura; Bomer, Johan G; Haarman, Ties; Ghiasi, Mahnaz; Schellhorn, Meike; Nachtegaal, Maarten; Odijk, Mathieu; van den Berg, Albert; Weckhuysen, Bert M; et al. (ACS catalysis, 2021)
The role that the α-Fe2O3/NiFeOOH interface plays in dictating the oxygen evolution reaction (OER) mechanism on hematite has been a source of intense debate for decades, but the chemical characteristics of this interface and its function are still ambiguous and subject to speculation. In this study, we employed operando X-ray absorption spectroscopy to investigate the interfacial dynamics at the α-Fe2O3/NiFeOOH interface. We uncovered the spontaneous formation of a FeOOH interfacial layer under (photo)electrochemical conditions. This FeOOH interfacial layer plays a role in the surface passivation of hematite and in accumulating the (photo)generated holes upon external potential application. This hole-accumulation process leads to the extraction of more (photo)generated holes from hematite before releasing them to NiFeOOH to carry out the water-splitting reaction, and it also explains the reason for the delay in the nickel oxidation process. Based on these observations, we propose a model where NiFeOOH acts mainly as an OER catalyst and a facilitator of holes extraction from hematite, while the interfacial FeOOH layer acts as a surface passivation and hole-accumulation overlayer.